Construction of bispectra for PCG signals - Жемчужкіна, Т. В.; Носова, Т. В.; Хамада, А. (НТУ «ХПІ», 2021)
To construct bispectra for separate segments of PCG such as sounds and murmurs we applied segmentation method based on averaged Shannon envelope. We got bispectrums of sounds and murmurs for different signals: normal and pathological. It can be seen that bispectra are non-zero, so signals are non-Gaussian. There is phase coupling between each two frequencies for each bispectrum. And also, the patterns for bispectra for each person are different in all groups.
Keywords: bispectra; PCG; Shannon envelope.